Comparison of surgical or nonsurgical treatment outcomes in patients with thoracolumbar fracture with Score 4 of TLICS: A randomized, single-blind, and single-central clinical trial. Issue 6 (February 2018) - Mohamadi, Alireza; Googanian, Ali; Ahmadi, Ali; Kamali, Alireza
Abstract: Background: Thoracolumbar fractures are among the most common types of damages caused to the spinal cord .Therefore, the aim of this study was the comparison of surgical or nonsurgical treatment outcomes in patients with thoracolumbar fracture with score 4 of the thoracolumbar injury classification and severity ( TLICS ) Methods: This study was clinical trial and double blind. Patients with thoracolumbar fracture with score 4 of TLICS entered at this research. We divided patients in 2 groups randomly (each group 25 patients) and then we followed patients for 1 year after start of treatment. We checked duration of bedridden and absence work, pain every 3 months for 1 year and radiography every 3 months for 1 year. Results: Pain in operative group was lower than nonoperative group ( P = . 02). Regional sagittal angles (RSA) in operative group was lower than nonoperative group in all time ( P = . 0001). Mean of time of return to work in operative group was lower than nonoperative group ( P = . 001). Conclusions: Pain and mean of time of return to work and RSA in operative group was lower than nonoperative group. The present data suggest the use of operative method in patients with thoracolumbar fracture with score 4 of TLICS.